2012
DOI: 10.1074/jbc.m112.382978
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Thymic Export and Increased Apoptosis Account for Regulatory T Cell Defects in Patients with Non-ST Segment Elevation Acute Coronary Syndrome

Abstract: Background:The mechanisms of Treg cell defects in NSTACS patients remain unclear. Results: The frequency of RTE-Treg and TREC content were markedly lower, and apoptosis of Treg cells in NSTACS patients was markedly increased. Conclusion: Impaired thymic output and enhanced apoptosis were responsible for Treg cell defects in NSTACS patients. Significance: Our findings explain the mechanisms of Treg cell defects in NSTACS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 66 publications
(26 reference statements)
3
53
0
1
Order By: Relevance
“…We also found that the gene expression levels of FOXP3 and GARP among patient PBMCs were reduced compared to the control group. Thus, our results support previous findings indicating that circulating CD4 + CD25 + FOXP3 + Tregs are reduced in patients with ACS [8,9,15,26]. …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We also found that the gene expression levels of FOXP3 and GARP among patient PBMCs were reduced compared to the control group. Thus, our results support previous findings indicating that circulating CD4 + CD25 + FOXP3 + Tregs are reduced in patients with ACS [8,9,15,26]. …”
Section: Discussionsupporting
confidence: 82%
“…Moreover, this difference was positively correlated with the frequency of CD4 + CD25 + GARP + Tregs, although there was no significant difference in IL-10 levels. These data are similar to those reported in previous studies [26,31] and may be explained by the finding that LAP (a precursor of TGF-β1) forms complexes with GARP; in particular, these complexes are downregulated in ACS [our unpublished data] and may therefore lead to a reduction in the level of TGF-β1.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Immune activation is considered the most significant feature in determining atherosclerotic plaque vulnerability. Specifically, the presence of activated inflammatory cells in plaque may increase vulnerability to and induce the occurrence of acute cardiovascular events, including ACS, through the release of matrix metalloproteinase, cytokines, and other mediators of inflammation [4,5,6,7,8,9]. Although substantial advances in this field have enhanced our understanding of atherosclerosis pathogenesis, the underlying molecular mechanisms have yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, Treg cells inhibit leukocyte-mediated myocardial damage and improve healing after MI through activation of M2-like myocardial macrophages and myofibroblast induction. 17 In addition, agedependent decrease of CD31 + T lymphocytes is associated with a progressive increase of CD31 − T lymphocytes and a subset of these cells, that is, CD31 − CD57 + CD28 − terminally differentiated senescent T cells, has been shown to have a detrimental effect on cardiac healing after MI because of enhanced production of inflammatory cytokines, such as interferon-γ and tumor necrosis factor-α.…”
Section: Article See P 99mentioning
confidence: 99%